Udział pielęgniarki w działaniach edukacyjnych podnoszących poziom świadomości pacjentów na temat profilaktyki raka jelita grubego = Participation of a nurse in educational activities increasing the level of patient awareness about the prevention of colorectal carcinoma - Raczyńska, Grażyna; Jędrzejkiewicz, Bernadeta; Sykut, Anna; Dobrowolska, Beata (Journal of Education, Health and Sport, 2017)
Raczyńska Grażyna, Jędrzejkiewicz Bernadeta, Sykut Anna, Dobrowolska Beata. Udział pielęgniarki w działaniach edukacyjnych podnoszących poziom świadomości pacjentów na temat profilaktyki raka jelita grubego = Participation of a nurse in educational activities increasing the level of patient awareness about the prevention of colorectal carcinoma. Journal of Education, Health and Sport. 2016;6(11):195-204. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.166115 http://ojs.ukw.edu.pl/index.php/johs/article/view/3986 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 22.10.2016. Revised 30.10.2016. Accepted: 11.11.2016. Udział pielęgniarki w działaniach edukacyjnych podnoszących poziom świadomości pacjentów na temat profilaktyki raka jelita grubego Participation of a nurse in educational activities increasing the level of patient awareness about the prevention of colorectal carcinoma Grażyna Raczyńska1, Bernadeta Jędrzejkiewicz2, Anna Sykut3, Beata Dobrowolska4 1Szpital Powiatowy w Rykach County Hospital in Ryki 2,3doktorantka, Wydział Nauk o Zdrowiu,Uniwersytet Medyczny w Lublinie PhD student, Faculty of Health Sciences, Medical University of Lublin 4Katedra Rozwoju Pielęgniarstwa; Uniwersytet Medyczny w Lublinie Department of Nursing Development, Medical University of Lublin mgr Grażyna Raczyńska, mgr Bernadeta Jędrzejkiewicz, mgr Anna Sykut, dr n. hum Beata Dobrowolska Słowa kluczowe: profilaktyka, rak jelita grubego, pielęgniarka, działania edukacyjne Key words: prophylaxis, colorectal carcinoma, nurse, education Streszczenie Wprowadzenie. Dane i wskaźniki epidemiologiczne raka jelita grubego są alarmujące. Nowotwór ten dotyka osób po 50 tym roku życia, wzrasta wraz z wiekiem, jest przyczyną około 12% zgonów nowotworowych. Szacuje się, że w 2025 roku liczba zachorowań wyniesie około 15 500 u mężczyzn i 9 100 u kobiet. Przykładem walki z rakiem jelita grubego jest Przesiewowy Program Badań. Należy podejmować działania poszerzające wiedzę ludzi na temat raka jelita grubego. Edukacja zdrowotna jest jedną z funkcji zawodowych pielęgniarek. Cel pracy. Celem pracy była analiza udziału pielęgniarki w działaniach edukacyjnych podnoszących poziom świadomości pacjentów na temat profilaktyki raka jelita grubego. Materiał i metoda. Badanie ankietowe zostało przeprowadzone wśród 107 (100%) aktywnych zawodowo pielęgniarek z województwa lubelskiego. Wyniki. W opinii respondentek osobą w największym stopniu odpowiedzialną za edukację pacjenta w zakresie profilaktyki raka jelita grubego jest lekarz rodzinny (n=84 ;78,5%). Najskuteczniejsze formy realizacji edukacji pacjentów to według respondentów indywidualne wręczanie zaproszeń na badania (n= 57; 53,3%) oraz pogadanki (n=56; 52,3%). Zdecydowana większość ankietowanych (n= 84; 78,5%) nie prowadzi edukacji wśród pacjentów. Badane, które takie działanie podejmują robią to przy okazji odwiedzin w środowisku (n= 16; 14,9%) i spotkań środowiskowych (n= 12; 11,2%). Badane pielęgniarki dość krytycznie oceniły poziom realizacji profilaktyki. Choć 48,6% (n=52) uznało go za poprawny to aż 34,6% (n=37) za słaby. Wnioski. Jedną z funkcji zawodowych pielęgniarki jest udzielanie świadczeń z dziedziny promocji zdrowia i edukacji zdrowotnej. Z badań wynika jednak, że udział pielęgniarki w działaniach edukacyjnych w profilaktyce raka jelita grubego jest ograniczony. Abstract Introduction. The data and epidemiological indicators of colorectal carcinoma are alarming. This cancer affects people over 50 years of age and increases with age. It is the cause of about 12% of cancer deaths. It is estimated that in year of 2025 the number of cases will be about 15500 in men and 9100 in women populations. An example of the fight against colorectal cancer is the Screening Research Program. Steps to expand the development of people knowledge about colorectal carcinoma should be undertaken and it is one of the professional functions of nurses. Aim of the study. The aim of the study was the analysis of participation of a nurse in educational activities increasing the level of patient awareness about the prevention of colorectal carcinoma. Materials and method. The survey was conducted among 107 (100%) professionally active nurses from Lublin Province. Results. In the opinion of respondents, the greatest responsibility for patient education in the scope of prevention of colorectal carcinoma takes a family doctor (GP) (n= 84; 78.5%). According to nurses surveyed, the most effective form of patients’ education is giving individual invitations for examination (n= 57; 53.3%) and short talks with patients (n=56; 52.3%). The vast majority of respondents (n= 84; 78.5%) does not conduct education among patients. Nurses who conduct education among patients usually do it in the occasion of visit in the patient’s home environment (n= 16; 14.9%) and community meetings (n=12; 11.2%). Nurses critically assessed the level of prophylaxis. Although, 48.6% (n=52) assessed it as correct, 34.6% (n=37) as week. Conclusions. One of the professional functions of a nurse is to provide health promotion and education. However, the research shows that the participation of a nurse in educational activities in the prevention of colorectal carcinoma is limited.